2015
DOI: 10.1088/0953-4075/48/16/164004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of molecular superrotors in an external magnetic field

Abstract: We excite diatomic oxygen and nitrogen to high rotational states with an optical centrifuge and study their dynamics in external magnetic field. Ion imaging is employed to directly visualize, and follow in time, the rotation plane of molecular superrotors. The two different mechanisms of interaction between the magnetic field and the molecular angular momentum in paramagnetic oxygen and non-magnetic nitrogen lead to the qualitatively different behaviour. In nitrogen, we observe the precession of the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…For strong fields, it was shown that the angular momentum becomes evenly distributed in the plane perpendicular to the magnetic field, and the precession is independent of the field strength. A comparison of the analytical derivations on one hand, and numerical simulations (reported here) as well as experimental observations (reported in [35,36]) on the other hand, showed a quantitative agreement for the weak field case and a qualitative agreement for the strong field case.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…For strong fields, it was shown that the angular momentum becomes evenly distributed in the plane perpendicular to the magnetic field, and the precession is independent of the field strength. A comparison of the analytical derivations on one hand, and numerical simulations (reported here) as well as experimental observations (reported in [35,36]) on the other hand, showed a quantitative agreement for the weak field case and a qualitative agreement for the strong field case.…”
Section: Discussionsupporting
confidence: 67%
“…The respective g-factor is of the order of 10 −4 [42]; for the considered field strengths of a few Tesla, this would correspond to precession periods of 100 ns and longer, clearly too slow to explain the observed effect (such a slow precession has been observed experimentally for nitrogen superrotors [36]). Instead, the interaction between N and B is mediated by the electronic spin S. The spin interacts with the magnetic field via the Zeeman interaction H ms , and with N via the spinrotation interactions H ss and H so .…”
Section: Rotation Of the Angular Momentum By The Magnetic Fieldmentioning
confidence: 84%
See 2 more Smart Citations
“…Optical centrifuge has recently been used for reaching extreme rotational states, known as molecular "superrotors" [23,24]. High degree of planar alignment has been demonstrated in the ensembles of centrifuged linear molecules [25]. Here, we extend this technique to the adiabatic alignment of asymmetric rotors.…”
mentioning
confidence: 99%